The cytopathology of mycobacterial infection. Issue 3 (22nd January 2016) - Michelow, Pamela; Omar, Tanvier; Field, Andrew; Wright, Colleen
Abstract : Mycobacterial infection, tuberculosis (TB) in particular, remains one of the world's deadliest communicable diseases in adults and particularly in children, in low and middle income countries. The combination of human immunodeficiency virus (HIV) and TB is often lethal with TB accounting for 25% of deaths in the HIV population. One of the cornerstones for reducing the TB epidemic is early case detection using high quality diagnostic techniques. Cytology, especially fine needle aspiration biopsy (FNAB) is able to diagnose mycobacterial infection in a rapid and cost‐effective manner without requiring surgery, thus allowing appropriate management to be quickly instituted. Confirmatory ancillary tests can effectively be performed on cytologic material. In this review, the pertinent cytomorphology of mycobacterial infection in various exfoliative and FNAB specimens is presented, in both immunocompetent and immunosuppressed patients. In the immunosuppressed, the typical cytomorphology of caseating granulomatous inflammation may not be seen but suppurative necrotic inflammation, mycobacterial spindle pseudotumour or a specimen comprised entirely of necrosis may be seen instead. This review includes discussion of currently available ancillary tests that can be performed on cytologic specimens. Diagn. Cytopathol. 2016;44:255–262. © 2016 Wiley Periodicals, Inc.